Strength of microbeads for the encapsulation of heat sensitive, hydrophobic components. (May 2016) - van Leusden, P.; den Hartog, G.J.M.; Bast, A.; Postema, M.; van der Linden, E.; Sagis, L.M.C.
Abstract: Hydrophobic food ingredients sensitive to degradation can be protected from their environment by microencapsulation. In an O/W1 /W2 system, these hydrophobic compounds are dissolved in oil droplets, dispersed within a gelled matrix microbead (W1 ), which forms a barrier. The stability and degree of protection delivered by the gel matrix depends on its structure and strength, which in turn depend on the gelling process. For heat sensitive ingredients this process is typically a cold-set gelling process. We investigated the effect of variations in matrix polymer (alginate and WPI aggregates), gelling agent (acid and calcium), and method of gelation (internal and external), on the ability of microbeads to retain oil droplets, and retain a spherical shape during the extraction from the oil phase. External gelation with CaCl2 nanoparticles gave the smoothest and strongest microbeads for both protein and alginate, which we attribute to the formation of a shell at the interface of the bead during gelation. Microbeads produced by internal calcium gelation (induced with CaCO3 nanoparticles and GDL) containing the same amount of calcium showed less integrity and gave a mixture of smooth and rough beads. About half of the microbeads produced by acid induced gelation of WPI aggregates (using GDL to lower the internal pH) remained intact. When the pH was brought further from the isoelectric point, fewer beads remained intact. The method of gelation proved to be more important for the microbead integrity than type of matrix polymer, and external gelling was clearly superior to internal and acid induced gelation. Graphical abstract: Highlights: Externally gelled alginate or WPI beads stay intact during the production process. External gelation gave stronger microbeads than internal gelation. External gelation was more significant to bead strength than type of polymer. Beads gelled by acid do not stay intact throughout the production process.